A phase II/III randomized, multicenter trial of prednisone/sirolimus versus prednisone/ sirolimus/calcineurin inhibitor for the treatment of chronic graft- versus -host disease: BMT CTN 0801 - Carpenter, Paul A.; Logan, Brent R.; Lee, Stephanie J.; Weisdorf, Daniel J.; Johnston, Laura; Costa, Luciano J.; Kitko, Carrie L.; Bolaños-Meade, Javier; Sarantopoulos, Stefanie; Alousi, Amin M.; Abhyankar, Sunil; Waller, Edmund K.; et al. (Haematologica (Roma), 2018)
Initial therapy of chronic graft- -host disease is prednisone ± a calcineurin-inhibitor, but most patients respond inadequately. In a randomized, adaptive, phase II/III, multicenter trial we studied whether prednisone/sirolimus or prednisone/sirolimus/photopheresis was more effective than prednisone/sirolimus/calcineurin-inhibitor for treating chronic graft- -host disease in treatment-naïve or early inadequate responders. Primary endpoints of this study were proportions of subjects alive without relapse or secondary therapy with 6-month complete or partial response in phase II, or with 2-year complete response in phase III. The prednisone/sirolimus/photopheresis arm closed prematurely because of slow accrual and the remaining two-drug three-drug study ended in phase II due to statistical futility with 138 evaluable subjects. The two-drug and three-drug arms did not differ in rates of 6-month complete or partial response (48.6% 50.0%, =0.87), or 2-year complete response (14.7% 15.5%, =0.90). Serum creatinine values >1.5 times baseline were less frequent in the calcineurin-inhibitor-free arm at 2 months (1.5% 11.7%, =0.025) and 6 months (7.8% 24.0%, =0.016). Higher adjusted Short Form-36 Physical Component Summary and Physical Functioning scores were seen in the two-drug arm at both 2 months ( =0.02 and =0.04, respectively) and 6 months ( =0.007 and =0.001, respectively). Failure-free survival and overall survival rates at 2 years were similar for patients in the the two-drug and three-drug arms (48.6% 46.2%, =0.78; 81.5% 74%, =0.28). Based on similar long-term outcomes, prednisone/sirolimus is a therapeutic alternative to prednisone/sirolimus/calcineurin-inhibitor for chronic graft- -host disease, being easier to administer and better tolerated.